The growth and human capital structure of new firms over the business cycle - Udo Brixy; Martin Murmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Recent research suggests that employment in young firms is more negatively impacted during economic downturns than employment in incumbent firms. This questions the effectiveness of policies that promote entrepreneurship to fight crises. We complement prior research that is mostly based on aggregate data by analyzing cyclical effects at the firm level. Using new linked employer-employee data on German start-ups we show that under constant human capital of the firms' founders, employment growth in less than 11=2-year-old start-ups reacts countercyclically and employment growth in older start-ups reacts procyclically. The young start-ups realize their countercyclical growth by hiring qualified labor market entrants who might be unable to find employment in incumbent firms during crises. This mechanism is highly important in economic and management terms and has not been revealed by prior research.
urn:nbn:de:bsz:180-madoc-415926
Keywords: E32; J23; L26; M13; L25; L11; D22; 330; Firm growth; Entrepreneurship; Business cycle; Crisis